Pengaruh Media Kartu Bilangan Terhadap Kemampuan Kognitif Anak Di TK IT El-Banna Sibuhuan Kecamatan Barumun Kabupaten Padang Lawas - Lisda Khairani Pulungan (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
The aim of this research is to find out: (1) how children's cognitive development at TKIT El – Banna Sibuhuan is, (2) the influence of number card media on children's cognitive abilities at TKIT El – Banna Sibuhuan. This research is quantitative research with the type of experimental research. The research design used a one-group pretest-posttest type pre-experiment. The instruments used consist of observation, documentation and tests. The data analysis technique uses descriptive statistics and carries out a